RoboLikha extension program for inclusive STEM and sustainable development - Helen Grace Gonzales; Ruvel J. Cuasito Sr.; Marjun S. Sequera; Camilo Jose S. Salvana; Troadio M. Barbosa; Dominic O. Cagadas; Romano A. Pimentel; Dexter L. Duat; Christine Marie J. Madrid; Geovani Pabilona; Rozano A. Pimentel; Justine Clarenz L. Auxilio; Jerry B. Halibas; Ellen Jane G. Gulben; Daxter William L. Gulben; Cran Leigh Mae A. Salamanca; John Huss E. Tongco; Kathleen E. Padrigalan; Maria Teresa M. Fajardo; Muslikhin Muslikhin (Jurnal Cakrawala Pendidikan, 2026)
This paper presents the outcomes of RoboLikha: Creative Technology for Inclusive STEM Learning, the flagship extension program of the College of Technology at the University of Science and Technology of Southern Philippines (USTP). The program was designed to address inequities in STEM education among underserved schools in Northern Mindanao through teacher training, student mentoring, community-centered implementation, and institutional partnerships aligned with the USTP CARES pillars and the UN Sustainable Development Goals. The program adopted a holistic and participatory framework that combined   caravans, training of trainers, workshops, research mentoring, and competitions. From 2023 to 2025, RoboLikha capacitated more than 200 teachers, engaged over 600 students, and reached more than 3,800 community participants across Region 10. Six investigatory projects were co-developed at Cagayan de Oro National High School, two of which received national recognition at the 2025 National Science and Engineering Fair. Teachers also transformed their participation into funded research outputs, demonstrating that extension work can directly enhance professional growth and curriculum innovation. These findings validate RoboLikha as a transformative and scalable model for inclusive STEM education. Looking ahead to 2030, the program aims to expand to ten fully engaged schools, institutionalize innovation expos, and cultivate Creative Tech champions to sustain robotics and creative technology integration nationwide.